Dose-Dependent, Antidepressant, and Anxiolytic Effects of a Traditional Medicinal Plant for the Management of Behavioral Dysfunctions in Animal Models - Hafiz Muhammad Asif; Abdul Hayee; Muhammad Rahil Aslam; Khalil Ahmad; Abdul Sattar Hashmi (SAGE Publishing, 2019)
The present work was carried out to assess the Onosma bracteatum anxiolytic and antidepressant properties. Swiss albino mice (male) were fed orally with hydroalcoholic extract at different doses 50, 100, and 200 mg 1 hour prior to test with the standard diazepam and fluoxetine. Anxiolytic and antidepressant activities were evaluated by using open field, elevated plus maze, force swimming, and tail suspension test. Results of open field test showed an increase in number of line crossing as well as number of rearing in dosage-dependent design. Although results of elevated plus maze test evidently showed antianxiety effect of O bracteatum by increasing the time spent in open arms along with decreasing the time spent in closed arms in dosage-dependent way. For the evaluation of antidepressant effect, O bracteatum diminished the immobility time and expanded mobility time in forced swim model in dosage-dependent way. Likewise, O bracteatum expanded time span of mobility along with diminished immobility time in tail suspension method in dosage-dependent way. Outcome demonstrated that plant at the dose of 200 mg/kg body weight showed significant potential which was similar to that standard diazepam and fluoxetine. Hence, O bracteatum may be used as potent natural psychotherapeutic agent against the mental disorders.